Method development for detection of E545A mutation PIK3CA gene in breast cancer patients using Tm Shift SYBR Green I qPCR - Fuad Al Ahwani; Desriani Desriani; Utut Widyastuti; Suharsono Suharsono (Indonesian Journal of Biotechnology, 2016)
E545A is one of the point mutations, and its frequency is high in PIK3CA gene (3.8%), particularly breast cancer patients in Singapore (13.8%) and Mexico (11.5%). In addition to induce breast cancer, the mutation also caused resistance of anti-HER2 in HER2 cancer subtype. The tremendous effect of this mutation was not supported by affordable detection method. This study aimed to develop a feasible and sensitive method of E545A detection. The developing method used Tm and Ct to identify samples. Based on optimization, the best condition was obtained at optimization 2 at annealing temperature of 65°C. At this condition, Tm and Ct of each sample were (a) exon 9 (78.4°C and 13.005±0.007) and (b) E5454A (80.4°C and 10.07±0.1). This method also demonstrated good precision as observed in variance coefficient of intra and inter assay (0). Thus, method for E5454A detection mutation was successfully developed.